The Probability of Union Membership in the Private Sector - Ng, Ignace (Relations industrielles / Industrial Relations, 1992)
The extent to which the probability of union membership is affected by demographic characteristics, occupational characteristics, and labor policies is examined. The results for the first 2 sets of factors show that married workers are more union-prone, whereas those with working spouses are less likely to become union members. Age is also significantly related to the probability of union membership, but education and gender are not. The results indicate that blue-collar workers and full-time employees are more likely to become union members. The most important finding, however, is that labor provisions do affect the probability of union membership. If the trade union movement wants to increase its membership, it should lobby for a reduction in the minimum support requirement during certification application and for a majority status based on those voting during certification elections. The movement may also want to support statutes protecting workers against their own unions.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Demographics; Labor Unions; Memberships; Probability; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Statistical analysis; Studies; Time series; Union membership